Human papilloma virus: knowledge of pharmacy academics at a college in Teresina (Research, Society and Development, 2020)
The Human Papillomavirus (HPV) causes a common infection and produces various manifestations. This infection becomes important for public health, due to be associated with malignancies of the reproductive tract in men and women, especially cervical cancer. This study aims to analyze and describe the knowledge of academics Pharmacy course of a Private School in Teresina about HPV. It is a quantitative-descriptive research and field. Of the 66 students, 35 are class "A" and 31 the class "B". Both in class "A", with 52% of students, as in "B", with a percentage of 48% reported having minimal information about HPV. Of the 66 students, about 90% responded that HPV is a sexually transmitted disease. There was a low level of knowledge of students about the modes of transmission, prevention and manifestation of genital HPV infection, as well as the risk factors for the development of cervical cancer. As for the Pap test, most have rudimentary information. Moreover, they answered incorrectly when they say that HPV can be diagnosed by Pap smear. About the existence of vaccination for prevention of HPV, most of the respondents confirmed they were acquainted. Based on the results obtained, it is concluded that a huge need for educational interventions in the academic population in order to promote accurate and appropriate information about HPV.